Domenico Giannetta, Tecniche per l’analisi della musica post-tonale - Paolo Tortiglione (Musica Docta)
Domenico Giannetta’s volume Tecniche per l’analisi della musica post-tonale [Techniques for the Analysis of Post-tonal Music] is an important analytical resource that fills a gap in Italian handbooks. In almost 500 pages, the book explores the problems of post-tonal musical analysis and examines the main lines of its development. The author focuses in particular on set theory, applying it to various musical repertoires, and offers practical tools for students and composers, emphasising the need for a critical and historical approach to musical analysis.